SGLT2 Inhibitor-Induced Ketonemia and Its Related Metabolic and Anti-Inflammatory Impacts in Adult Patients with Type 2 Diabetes: SGLT2 inhibitor-induced ketonemia in type 2 diabetes - Karimi, Fariba; Arya, Arash (Iranian Journal of Pharmaceutical Sciences, 2023)
Ketosis and attenuation of low-grade inflammation have been reported after consumption of sodium-glucose cotransporter-2 (SGLT2) inhibitors, but their mechanism and metabolic consequences have not been clearly defined. This clinical trial study aimed to assess SGLT2 inhibitor-induced ketonemia and its association with metabolic profiles and interleukin 6 (IL-6) levels in patients with type 2 diabetes mellitus (T2D). Biochemical variables, including fasting blood sugar (FBS), beta-hydroxybutyrate (BOBH), uric acid (UA), phosphate, insulin, glucagon, adrenocorticotropic hormone (ACTH), cortisol, and IL-6, were measured in 77 patients with T2D before and one month after treatment with empagliflozin (38 patients) and compared with a matched control group (39 patients). The patients in the intervention group received metformin and 10 mg empagliflozin, while those in the control group received metformin alone. The results revealed a significant decrease in IL-6, UA, FBS, glycated hemoglobin (HbA1C), body mass index (BMI), blood pressure, and the homeostasis model assessment–estimated insulin resistance (HOMA-IR) index after one month in the intervention group. However, the BOHB concentrations were significantly higher only in the empagliflozin recipients (p=0.040), with no symptoms or signs of ketoacidosis. Despite the increase in the concentration of BOHB, no significant difference was observed regarding insulin, glucagon, ACTH, and cortisol levels before and after taking empagliflozin. Besides, both groups observed a positive correlation between BOHB and UA levels (r=0.680, p=0.0001 in the empagliflozin group and r=0.646, p=0.002 in controls). Nevertheless, HOMA-IR and UA concentrations decreased significantly only in the intervention group (p=0.020 and p=0.011, respectively). At the end of the study, IL-6 levels showed a significant reduction within the groups and more in the intervention group compared to the controls. IL-6 levels were positively correlated to HOMA-IR (r=0.401, p=0.013) in the intervention group, but no relationship was detected between IL-6 and BMI, BOHB, UA, and insulin concentrations in the two groups. Based on the results, SGLT2 inhibitor-associated ketonemia was independent of changes in the insulin, glucagon, or cortisol levels. However, low-grade ketosis was associated with improved insulin sensitivity. The results also suggest that SGLT2 inhibitors possess anti-inflammatory activity, possibly mediated by their ability to reduce insulin resistance.